2010
DOI: 10.1007/s11099-010-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, chlorophyll fluorescence, inorganic ion and organic acid accumulations of sunflower in responses to salt and salt-alkaline mixed stress

Abstract: Sunflowers were treated with mixing proportions of NaCl, Na 2 SO 4 , NaHCO 3 , and Na 2 CO 3 . Effects of salt and saltalkaline mixed stress on growth, photosynthesis, chlorophyll fluorescence, and contents of inorganic ions and organic acids of sunflower were compared. The growth of sunflower decreased with increasing salinity. The contents of photosynthetic pigments did not decrease under salt stress, but their contents decreased sharply under salt-alkaline mixed stress. Net photosynthetic rates, stomatal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 38 publications
(55 reference statements)
4
43
0
1
Order By: Relevance
“…Such observations of higher A and g s in saline conditions by tolerant over sensitive genotypes, have been reported in soybean (Lu et al, 2009) and rice (Moradi and Ismail, 2007). Moreover, increased WUE in saline conditions was evident in tolerant genotypes of sunflower (Liu and Shi, 2010) and wheat (Yang et al, 2008), as found here for Genesis836 in chickpea, possibly assisting these genotypes to cope with reduced leaf water potential in saline conditions. Salt stress can affect A in plants via stomatal closure leading to decreased CO 2 availability or by changing the photosystems and photosynthetic metabolism (Chaves et al, 2009).…”
Section: Photosynthesis In Salt Stressed Chickpea Is Limited By Non-ssupporting
confidence: 85%
“…Such observations of higher A and g s in saline conditions by tolerant over sensitive genotypes, have been reported in soybean (Lu et al, 2009) and rice (Moradi and Ismail, 2007). Moreover, increased WUE in saline conditions was evident in tolerant genotypes of sunflower (Liu and Shi, 2010) and wheat (Yang et al, 2008), as found here for Genesis836 in chickpea, possibly assisting these genotypes to cope with reduced leaf water potential in saline conditions. Salt stress can affect A in plants via stomatal closure leading to decreased CO 2 availability or by changing the photosystems and photosynthetic metabolism (Chaves et al, 2009).…”
Section: Photosynthesis In Salt Stressed Chickpea Is Limited By Non-ssupporting
confidence: 85%
“…Accumulation of organic acids was one regular defense response in plants exposed to stress conditions, especially in salt and alkaliinduced osmotic stress or nutrient deficiency (Li and Shi, 2010;Carvalhais et al, 2011). In the present study, SNP treatment significantly increased contents of acetate, malate and citrate in cucumber leaves under alkali stress, which was exactly in accordance with the enrichment of organic acid metabolic process (GO: 0006082) and carboxylic acid biosynthetic process (GO: 0046394).…”
Section: Discussionsupporting
confidence: 84%
“…Accumulating evidence suggests that photosynthesis is greatly inhibited under excessive sodium carbonate conditions via the decrease of chlorophyll biosynthesis and photosystem II efficiency (Yang et al 2008a;Liu and Shi 2010;Bu et al 2012). Our proteomic analysis showed 20 photosynthetic proteins were differentially expressed in H. tuberosus subjected to Na 2 CO 3 stress.…”
Section: Photosynthesismentioning
confidence: 71%
“…Studies have shown that alkali stress also significantly affects photosynthesis and photosynthetic electron transport. In rice, sunflower and thirty switchgrass, alkali stress caused a sharp reduction in photosynthetic parameters and chlorophyll fluorescence (Liu and Shi 2010;Bu et al 2012;Hu et al 2015). The same situation occurred in halophyte Chloris virgate except the net photosynthetic rate (P N ) was increased slightly under moderate alkali stress (Yang et al 2008a).…”
mentioning
confidence: 79%